PENGARUH KONTEN PROMOSI, ONLINE CUSTOMER REVIEW, DAN BRAND AWARENESS TERHADAP KEPUTUSAN PEMBELIAN “KOMPIANG LEJONG” SNACK KHAS MANGGARAI-NUSA TENGGARA TIMUR - Antonius Mariano Agung Mayosphildin; Teguh Widodo; Tin Agustina Karnawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the influence of promotional content, online customer reviews, and brand awareness on purchase decisions for Kompiang Lejong, a traditional snack from Manggarai, East Nusa Tenggara. The current phenomenon of increasing competition among local SMEs in the food sector requires business owners to implement digital marketing strategies to attract costomer interest in the digital economy era. This research employs a quantitative approach using a digital questionnaire distributed to customers who are familiar with and have purchased Kompiang Lejong products. The primary data collected through a Likert-scale questionnaire were analyzed using Partial Least Square (PLS) to examine the relationships among the variables. The results show that promotional content has a positive and significant effect on purchase decisions, indicating that attractive and informative visual messages can enhance customer interest. Online customer reviews also have a significant influence on purchase decisions, as positive reviews strengthen customers’ trust in the product. In addition, brand awareness positively affects purchase decisions because a higher level of brand recognition increases customers’ tendency to choose the product. Simultaneously, all three variables have a significant impact on purchase decisions. These findings reinforce the AIDA theory and digital custmer behavior theory, emphasizing that attention, interest, and brand awareness are crucial factors influencing customer purchasing behavior in the digital era.